Amperometric galectin-3 immunosensor-based gold nanoparticle-functionalized graphitic carbon nitride nanosheets and core–shell Ti-MOF@COFs composites. Issue 38 (23rd September 2020) - Yola, Mehmet Lütfi; Atar, Necip
Abstract : Antigen galectin-3 (GL-3), a member of β-galactoside proteins indicates cardiac fibrosis and is a significant biomarker for monitoring heart failure risk and death risk. Abstract : Antigen galectin-3 (GL-3), a member of β-galactoside proteins indicates cardiac fibrosis and is a significant biomarker for monitoring heart failure risk and death risk. In this study, a novel sensitive amperometric method for antigen GL-3 detection is developed based on gold nanoparticle-functionalized graphitic carbon nitride nanosheets (g-C3 N4 @Au NPs) as the sensor platform and Ti-based metal organic framework (Ti-MOF, NH2 -MIL-125)@covalent organic frameworks (COFs) composite for the signal amplification. The Ti-MOF@COF composite not only facilitates the penetration of antibody proteins into pore channels, but also the highly stable antigen–antibody interactions. The prepared sensor platform and signal amplification material are characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD) method, X-ray photoelectron spectroscopy (XPS), UV–vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The amperometric technique is utilized to achieve antigen GL-3 detection in plasma samples. The immunosensor demonstrates a wide linearity range (0.0001–20.0 ng mL −1 ) and a low detection limit (0.025 pg mL −1 ). Finally, the prepared immunosensor shows high stability and selectivity under optimum conditions.